2010
DOI: 10.1111/j.1471-0528.2009.02455.x
|View full text |Cite
|
Sign up to set email alerts
|

The association between Mycoplasma genitalium and pelvic inflammatory disease after termination of pregnancy

Abstract: The prevalence and complications of Mycoplasma genitalium and Chlamydia trachomatis infections among women undergoing termination of pregnancy were studied in this nested case-control study at Malmo University Hospital, Sweden, during 2003 to 2007. The study comprised 2079 women presenting for termination of pregnancy. Forty-nine women with M. genitalium infection and 51 women with C. trachomatis infection, together with 168 negative control women, were evaluated. The prevalences of M. genitalium and C. tracho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
51
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(58 citation statements)
references
References 8 publications
3
51
0
4
Order By: Relevance
“…The first evidence of an association came from a Japanese study, reported in 1997 (225), in which M. genitalium was detected in the cervices of 5 (9%) of 57 women with cervicitis but in none of 79 women without the condition. Subsequently, the results of other studies (2,4,11,23,48,57,80,89,137,139,148,163,165,225), shown in Fig. 5, to a large extent attest to M. genitalium having a significant role in causing cervicitis.…”
Section: Cervicitismentioning
confidence: 95%
“…The first evidence of an association came from a Japanese study, reported in 1997 (225), in which M. genitalium was detected in the cervices of 5 (9%) of 57 women with cervicitis but in none of 79 women without the condition. Subsequently, the results of other studies (2,4,11,23,48,57,80,89,137,139,148,163,165,225), shown in Fig. 5, to a large extent attest to M. genitalium having a significant role in causing cervicitis.…”
Section: Cervicitismentioning
confidence: 95%
“…Data on the prevalence of NG infection in the general population do not seem to exist. Studies based on females undergoing TOP in a hospital setting mentioned infection rates as follows: CT 2.8% to 15.74%; MG 0.98% to 8.7%; NG 0.67% to 3% (12,(15)(16)(17)(18). Reasons for these wide ranges are multifarious, e.g.…”
Section: ü1 Introductionmentioning
confidence: 99%
“…In men, M. genitalium is a significant cause of both acute and chronic nongonococcal urethritis (NGU) (5-7) and is estimated to account for 15% to 25% of cases of NGU in some populations (2). In women, M. genitalium has been significantly associated with both cervicitis (2, 8-10) and pelvic inflammatory disease (2,(11)(12)(13)(14), and it has been identified in up to 7.3% of women in high-risk populations (15). In Australia, M. genitalium has been reported to account for between 4.5% and 9% of cases of NGU (16, 17), while it was identified in 4% of women attending a Sydney sexual health clinic and was the second most common cause of cervicitis (9).…”
mentioning
confidence: 99%